2021
DOI: 10.1002/uog.22037
|View full text |Cite
|
Sign up to set email alerts
|

Application of ultrasound‐based radiomics technology in fetal‐lung‐texture analysis in pregnancies complicated by gestational diabetes and/or pre‐eclampsia

Abstract: Using ultrasound-based radiomics technology to analyze fetal-lung texture, fetal lungs from pregnancies grouped according to whether they were affected by gestational diabetes mellitus (GDM) and/or pre-eclampsia (PE) could be distinguished from each other and from fetal lungs of normal pregnancies, and lungs from pregnancies at different gestational ages could be distinguished. What are the clinical implications of this work?These results support the possibility that this technology may be helpful in non-invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 31 publications
0
37
0
1
Order By: Relevance
“…The results of these studies indicate that some gestational diseases can affect FLM. The latest research by Du et al [ 34 ] found that GDM, PE, and normal fetal lungs can be quickly and accurately classified by ultrasound-based radiomics techniques, indicating that differences in fetal lung development between gestational diseases (GDM and PE), and normal pregnancies were highly significant. Our study used DL algorithms to extract information from numerous normal fetal lung ultrasound images to establish a normal fetal lung grading model that can help to identify abnormal lung development that can result from some gestational diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies indicate that some gestational diseases can affect FLM. The latest research by Du et al [ 34 ] found that GDM, PE, and normal fetal lungs can be quickly and accurately classified by ultrasound-based radiomics techniques, indicating that differences in fetal lung development between gestational diseases (GDM and PE), and normal pregnancies were highly significant. Our study used DL algorithms to extract information from numerous normal fetal lung ultrasound images to establish a normal fetal lung grading model that can help to identify abnormal lung development that can result from some gestational diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to CT or MRI, radiomics on US images is a relatively new and less explored type of analysis. Nonetheless, it is gaining gound [53][54][55][56] .…”
Section: Discussionmentioning
confidence: 99%
“…Besides being employed for oncology diseases, Du et al. ( 115 ) utilized the profile of gestational diabetes mellitus, pre-eclampsia, and normal pregnancies to assess fetal lung and gestational age in gestational diabetes mellitus/pre-eclampsia, supporting the research of neonatal respiratory disorders. Salvatore et al.…”
Section: Some Case Studies and Applicationsmentioning
confidence: 99%